2011
DOI: 10.1002/jccs.201190015
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Catechol on Boron‐doped Diamond Electrode Modified with Au/TiO2 Nanorod Composite

Abstract: Au/TiO 2 nanorod composites with different ratios of [TiO 2 ]: [Au] have been prepared by chemically reducing AuCl 4 -on the positively charged TiO 2 nanorods surface and used to modify boron-doped diamond (BDD) electrodes. The electrochemical behaviors of catechol on the bare and different Au/TiO 2 nanorod composites-modified BDD electrodes are studied. The cyclic voltammetric results indicate that these different Au/TiO 2 nanorod composites-modified BDD electrodes can enhance the electrocatalytic activity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The prepared modified electrode presented a linear range for dopamine from 5.0 to 1200 M with a detection limit of 3.4 M. In addition, a phenol biosensor was constructed by immobilizing tyrosinase in a vapor deposition TiO 2 sol-gel nano-matrix, which provided a biocompatible microenvironment for retaining the activity of the entrapped enzyme and a low mass transport barrier to the enzyme substrates [19]. The biosensor exhibited a fast response (less than 5 s) and a linear range for phenol determination from 0.12 to 260 M with a detection limit of 0.1 M. Furthermore, one dimensional TiO 2 nanomaterials were also reported for the amperometric detection of phenolic compounds [20]. For instance, a phenol sensor was fabricated by deposition of Au/TiO 2 nanorod nanocomposites on boron-doped diamond (BDD) electrodes.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The prepared modified electrode presented a linear range for dopamine from 5.0 to 1200 M with a detection limit of 3.4 M. In addition, a phenol biosensor was constructed by immobilizing tyrosinase in a vapor deposition TiO 2 sol-gel nano-matrix, which provided a biocompatible microenvironment for retaining the activity of the entrapped enzyme and a low mass transport barrier to the enzyme substrates [19]. The biosensor exhibited a fast response (less than 5 s) and a linear range for phenol determination from 0.12 to 260 M with a detection limit of 0.1 M. Furthermore, one dimensional TiO 2 nanomaterials were also reported for the amperometric detection of phenolic compounds [20]. For instance, a phenol sensor was fabricated by deposition of Au/TiO 2 nanorod nanocomposites on boron-doped diamond (BDD) electrodes.…”
Section: Introductionmentioning
confidence: 95%
“…Due to the advantages such as biocompatibility, chemical and electrochemical inertness, high specific surface area and strong immobilization ability, TiO 2 nanomaterials have been applied in the construction of electrochemical biosensors for the determination of phenolic compounds in recent years [18][19][20]. For example, a new TiO 2 -carbon phenolic biosensor was developed by incorporating plant tissues containing enzyme polyphenol oxidase into a uniform mixture consisting of TiO 2 nanoparticles, graphite powder and silica sol [18].…”
Section: Introductionmentioning
confidence: 99%
“…The combined merits of PM and AuNPs accelerated the electron transfer rate, resulting in CT′s reversibility toward the modified sensor [90] . Wei and co‐workers [91] prepared a CT sensor by modifying BDD using an Au/TiO 2 nanorod composite. For the preparation of the Au/TiO 2 nanorod composite, they used a chemical method to reduce AuCl 4 − on the positively charged TiO 2 .…”
Section: Individual Detection Of Ctmentioning
confidence: 99%
“…reported that the TiO 2 /BDD composite electrodes fabricated by the metal-organic chemical vapor deposition system could efficiently degrade the reactive yellow 15 and reduce the hexavalent chromium under the UV light irradiation. Wei et al [ 27 ] found that a Au/TiO 2 nanorod modified the BDD electrode obtained by the chemical reduction method showed the favorable electro-catalytic activity toward the detection of catechol with a fast response, a high sensitivity, and a low detection limit, as compared with the bare BDD electrode. Therefore, the TiO 2 modification of the electrode is a potentially effective way to enhance the electrocatalytic performance of the BDD.…”
Section: Introductionmentioning
confidence: 99%